2012
DOI: 10.1103/physreve.86.056307
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation- and streaming-induced microparticle velocities determined by microparticle image velocimetry in an ultrasound symmetry plane

Abstract: We present microparticle image velocimetry measurements of suspended microparticles of diameters from 0.6 to 10 μm undergoing acoustophoresis in an ultrasound symmetry plane in a microchannel. The motion of the smallest particles is dominated by the Stokes drag from the induced acoustic streaming flow, while the motion of the largest particles is dominated by the acoustic radiation force. For all particle sizes we predict theoretically how much of the particle velocity is due to radiation and streaming, respec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
218
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(225 citation statements)
references
References 37 publications
7
218
0
Order By: Relevance
“…However, for smaller particles, the focusing by the acoustic radiation force is hindered by the drag force from the suspending liquid, which is set in motion by the generation of an acoustic streaming flow [2,3]. This limits the use of acoustophoresis to manipulate submicrometer particles, relevant for application within medical, environmental, and food sciences, and it underlines a need for better understanding of acoustic streaming and ways to circumvent this limitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for smaller particles, the focusing by the acoustic radiation force is hindered by the drag force from the suspending liquid, which is set in motion by the generation of an acoustic streaming flow [2,3]. This limits the use of acoustophoresis to manipulate submicrometer particles, relevant for application within medical, environmental, and food sciences, and it underlines a need for better understanding of acoustic streaming and ways to circumvent this limitation.…”
Section: Introductionmentioning
confidence: 99%
“…We only consider acoustic perturbation in fluids, and treat the surrounding solid material as ideal rigid walls, a good approximation for water channels in glass-silicon systems. Moreover, extensive theoretical and experimental work [2,3,10,11,19,21] has shown that the adiabatic model describes the observed phenomena qualitatively correctly, while thermoviscous effects may lead to relative quantitative changes up to 30%. Thus by employing an adiabatic model, we can provide an analysis of experimental relevance while at the same time restricting the complexity and vast parameter space of the full problem.…”
Section: Basic Adiabatic Acoustic Theorymentioning
confidence: 99%
“…The visualization and tracking of particles are generally performed using particle image velocimetry (PIV) as in Manneberg et al [8,16] and Barnkob et al [17]. The tracking of particle motion under ASWs using the astigmatism particle tracking velocity (APTV) technique was also reported by Muller et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the very different displacement fields in the surrounding chip material, which is represented as the magnitude of the real part of the displacement jReðuÞj by the color plot (from blue zero, via green, to red maximum), both systems exhibit a nearly perfect horizontal standing pressure wave ReðpÞ (the color plot from blue minimum, through white, to red maximum or line plot in the inset) in the fluid. This occurrence has been observed experimentally [25][26][27], and it is ideal for forcing the particles to the vertical pressure nodal plane in the center of the channel. By definition of f acp , the orientation θ is close to unity in both systems.…”
Section: Example Of Identifying Good Acoustophoresismentioning
confidence: 99%
“…The first numerical optimization studies of acoustophoretic devices have also been performed recently, illustrating a procedure to obtain optimal acoustophoretic forces by changing the geometrical parameters of the device [21]. Other studies involve numerical characterization of the acoustic pressure wave in the microchannel and subsequent computation of particle trajectories by means of numerical integration [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%